Measuring calcium content in plants using NEXAFS spectroscopy - Rongpipi, Sintu; Barnes, William J.; Siemianowski, Oskar; Del Mundo, Joshua T.; Wang, Cheng; Freychet, Guillaume; Zhernenkov, Mikhail; Anderson, Charles T.; Gomez, Esther W.; Gomez, Enrique D. (Frontiers in Plant Science, 2023)
Calcium is important for the growth and development of plants. It serves crucial functions in cell wall and cell membrane structure and serves as a secondary messenger in signaling pathways relevant to nutrient and immunity responses. Thus, measuring calcium levels in plants is important for studies of plant biology and for technology development in food, agriculture, energy, and forest industries. Often, calcium in plants has been measured through techniques such as atomic absorption spectrophotometry (AAS), inductively coupled plasma–mass spectrometry (ICP-MS), and electrophysiology. These techniques, however, require large sample sizes, chemical extraction of samples or have limited spatial resolution. Here, we used near-edge X-ray absorption fine structure (NEXAFS) spectroscopy at the calcium L- and K-edges to measure the calcium to carbon mass ratio with spatial resolution in plant samples without requiring chemical extraction or large sample sizes. We demonstrate that the integrated absorbance at the calcium L-edge and the edge jump in the fluorescence yield at the calcium K-edge can be used to quantify the calcium content as the calcium mass fraction. Using onion epidermal peels with age-dependent calcium mass ratios, we developed a NEXAFS calibration curve and validated it using ICP-MS. Next, we used NEXAFS to estimate the calcium mass ratio in hypocotyls of a model plant, Arabidopsis thaliana, which has a cell wall composition that is similar to that of onion epidermal peels. These results show that NEXAFS spectroscopy performed at the calcium edge provides an approach to quantify calcium levels within plants, which is crucial for understanding plant physiology and advancing plant-based materials.